Tetranuclear lanthanide complexes showing magnetic refrigeration and single molecule magnet behavior. (10th May 2019) - Yu, Hong; Yang, Jia-Xing; Han, Ju-Qing; Li, Peng-Fei; Hou, Yin-Ling; Wang, Wen-Min; Fang, Ming
Abstract : Four tetranuclear lanthanide complexes were fabricated and characterized.1 exhibits cryogenic magnetic refrigeration property and3 displays slow relaxation of the magnetization. Abstract : Three tetranuclear lanthanide complexes: {[Ln4 (L)6 (pbd)4 (μ3 -OH)2 ]·2CH3 CN} (Ln = Gd (1), Tb (2), Dy (3); HL = 5-(benzylideneamino)quinolin-8-ol, pbd = 1-phenylbutane-1, 3-dione) were fabricated and structurally characterized. Compounds1–3 are isostructural belonging to the triclinic system with space group P 1̄. The core of the complexes contains a tetranuclear arrangement of Ln III ions which is held together by two pyramidal μ3 -OH − ions and six μ2 phenol hydroxyl oxygen atoms derived from six L − ligands. Magnetic studies indicated that1 exhibits cryogenic magnetic refrigeration properties (maximum −Δ S m = 21.41 J K −1 kg −1, Δ H = 7 T at 2.0 K), whereas compound3 exhibits slow relaxation of the magnetization with an energy barrier (Δ E / k B ) of 81.48 K and τ 0 = 6.48 × 10 −8 s.